Traumatic Palatal Defect Closure With Prosthesis Post Surgical Reconstruction: A Team Approach - Martina, Nungki Ratna; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Jurnal Plastik Rekonstruksi, 2012)
Background: Palatal defect may be a result of congenital malformations, trauma or tumors. In most maxillopalatal trauma, surgical reconstruction is required to restore the function and appearance. Any palatal defect caused by maxillopalatal loss that cannot be achieved with surgical reconstruction needs special and comprehensive treatment. This can be done by prosthodontist prosthesis rehabilitation.Patients and Methods: A 20-year-old man underwent open reduction and internal fixation for severe maxillopalatal fracture and palatal loss. Intraoperative, the palatal defect could not be approximated due to palatal loss. In 3-month-follow up, there was a palatal defect and slight malocclusion due to anterior dental loss. Instead of performing complicated surgical procedures, we collaborate with the prosthodontist to assemble prosthesis with dental prosthesis that accommodate the closure of defect and improve appearance aesthetically. Result: The use of prosthesis improves functional and psychological wellbeing. It does not only close the palatal defect, but it also fills the anterior dental loss thus overcoming the malocclusion. Satisfying functional and aesthetic outcome was achieved. Summary: Rehabilitation of maxillopalatal defect has been well defined for prosthodontists and surgeons. A successful prosthetic design for functional restoration of the palatal defect utilizes the remaining palate and dentition to maximize the support, stability and appearance. In this case,prosthodontist and dentition prosthesis was used as modalities that offer simple solution to close the palatal defect compared to a more complicated surgical intervention.